Design of Perchlorotriphenylmethyl (PTM) Radical‐Based Compounds for Optoelectronic Applications: The Role of Orbital Delocalization - Diez‐Cabanes, Valentín; Seber, Gonca; Franco, Carlos; Bejarano, Francesc; Crivillers, Nuria; Mas‐Torrent, Marta; Veciana, Jaume; Rovira, Concepció; Cornil, Jérôme (Chemphyschem, 2018)
Perchlorotriphenylmethyl (PTM) radical‐based compounds are widely exploited as molecular switching units. However, their application in optoelectronics is limited by the fact that they exhibit intense absorption bands only in a narrow range of the UV region around 385 nm. Recent experimental works have reported new PTM based compounds which present a broad absorption in the visible region although the origin of this behavior is not fully explained. In this context, Time‐Dependent Density Functional Theory (TD‐DFT) calculations have been performed to rationalize the optical properties of these compounds. Moreover, a new compound based on PTM disubstituted with bistriazene units has been synthetized and characterized to complete the set of available experimental data on related compounds. The results point to the delocalization of the Highest Occupied Molecular Orbital (HOMO) of the substituents along the PTM core as the origin of the new high absorption bands in the visible region. As a consequence, the absorption of the PTM‐based compounds can be tuned via the choice of the nature of the donor substituent, type of connection, and number of substituents. Organic radicals for optoelectronics: Time‐dependent density functional theory (TD‐DFT) calculations are combined with experimental data to shed light on the complex mechanism that drives the absorption properties of perchlorotriphenylmethyl (PTM) radical‐based compounds, where the radical PTMs act as electron acceptors (A) and the substituents as electron donors (D). The results point to the relevance of the nature, type of connections, and number of donor substituents for controlling the absorption of these D–A organic radical compounds in the visible region (see picture).